Asset pricing with unforeseen contingencies☆ - KRAUS, A; SAGI, J (Journal of Financial Economics, 2006)
We investigate an economy of heterogeneous agents that cannot specify all exogenous welfare-relevant events and consequently view the impact of unforeseen contingencies as utility shocks. In this setting we characterize an appropriate market equilibrium concept when securities can trade only on demand- and price-contingent events. We establish the existence of an equilibrium for a class of parametric models in which aggregating taste shocks across agents can lead to nonconsumption pricing factors. To fit the stylized facts, (i) non consumption factors must dominate the pricing kernel and contribute to the variation of the wealth-consumption ratio, (ii) markets must be incomplete and the set of claims that are traded endogenously determined, (iii) agents’ preferences with respect to unforeseen contingencies must be non-expected utility, and, (iv) although non-consumption pricing factors can be conditionally uncorrelated with aggregate consumption shocks, they must be correlated with shocks to expected consumption growth.